PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR PUKULAN DRIVE TENIS MEJA - Dartini, Ni Putu Dwi Sucita; Artanayasa, I Wayan; Spanayawati , Ni Luh Putu (Universitas Pendidikan Ganesha, 2023)
This research aims to determine the influence of the Students Teams Achievement Division (STAD) cooperative learning model on table tennis drive learning outcomes, the influence of the Teams Games Tournament (TGT) cooperative learning model on table tennis drive learning outcomes, differences in the influence of cooperative learning models on table tennis drive learning outcomes, and differences in the influence of the STAD and TGT learning models on table tennis drive learning outcomes. The research method uses an experimental method with a pre-test – post-test control group design. The population in this study were all students of the FOK Undiksha Physical Education and Physical Education Study Program. The sample in this research was fifth semester students who took TP courses. Table Tennis lessons totaling 56 people divided into 3 classes. Class A is an experimental class treated with the TGT learning model, class B is a control class treated with a conventional learning model and class C is an experimental class treated with a TGT learning model. The research results show that there is an influence of the STAD cooperative learning model on table tennis drive learning outcomes, there is an influence of the TGT cooperative learning model on table tennis drive learning outcomes, there is a difference in the influence of the cooperative learning model and the conventional learning model on the learning outcomes of table tennis drive, and there is no difference in influence between the STAD cooperative learning model and the TGT learning model